Forest restoration and agroforestry as natural climate solutions - Binkovskyi, A. О.; Біньковський, Артем Олександрович (Харківський національний автомобільно-дорожній університет, 2025)
The article examines forest-based climate solutions from 2020 to 2050, including deforestation avoidance, forest restoration, and agroforestry. It analyzes regional mitigation potential, carbon sequestration, biodiversity benefits, and socio-economic factors essential for sustainable implementation and climate change mitigation.
Відновлення лісів та агролісівництво як природні кліматичні рішення
Keywords: Climate change mitigation; Afforestation; Reforestation; Agroforestry; Forest conservation; Carbon sequestration; Sustainable development; Forest management; Greenhouse gas emissions; Forest natural climate solutions; відновлення лісів; агролісівництво; природні кліматичні рішення; поглинання вуглецю; пом’якшення змін клімату; Україна; 631.5; 10.30977/BUL.2219-5548.2025.109.0.41